Fantastic realities: 49 mind journeys and a trip to Stockholm - Wilczek, Frank; Devine, Betsy (World Scientific Publishing Co. Pte. Ltd, 2006)
The fantastic reality that is modern physics is open for your exploration, guided by one of its primary architects and interpreters, Nobel Prize winner Frank Wilczek. Some jokes, some poems, and extracts from wife Betsy Devine's sparkling chronicle of what it's like to live through a Nobel Prize provide easy entertainment. There's also some history, some philosophy, some exposition of frontier science, and some frontier science, for your lasting edification. 49 pieces, including many from Wilczek's award-winning Reference Frame columns in Physics Today, and some never before published, are gathered by style and subject into a dozen chapters, each with a revealing, witty introduction.